Nonagricultural Demand Causes Agricultural Land Values to Increase - John E. Reynolds (EDIS)
The 2004 Florida Land Value Survey results indicate that the value of all types of agricultural land increased substantially in all regions of the state from 2003 to 2004. The market for agricultural land was very active this past year and the rate of increase in land values was particularly high in the South region. The percentage change in most categories was in the double-digits. Survey respondents indicated that increases in agricultural land values were primarily due to strong nonagricultural demand for land. Agricultural land values vary by the type of land use and geographic area. The survey results indicate that the average value for agricultural land ranges from approximately $1,500 per acre for unimproved pasture and farm woods in the Northwest region to over $6,500 for orange groves in the South region. This is EDIS document FE545, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published April 2005.